Learning religion : anthropological approaches. (Methodology and history in anthropology ;, 2009)
As we enter the 21st century, it becomes increasingly difficult to envisage a world detached from religion or an anthropology blind to its study. Yet, how people become religious is still poorly studied. This volume gathers some of the most distinguished scholars in the field to offer a new perspective for the study of religion, one that examines the works of transmission and innovation through the prism of learning. They argue that religious culture is socially and dynamically constructed by agents who are not mere passive recipients but engaged in active learning processes. Finding a middle way between the social and the cognitive, they see learning religions not as a mechanism of “downloading” but also as a social process with its relational dimension.